Microstructural analysis of brazing sapphire and inconel 600 for sensor applications - Zaharinie, T.; Yusof, F.; Fadzil, M.; Hamdi, M.; Ariga, T. (Maney Publishing, 2014)
The development of sapphire-based sensors for gas pressure application is growing in demand because of their appealing characteristics that could withstand high temperatures and harsh operating conditions. However, the joining process of sapphire to other materials, especially metals, is difficult to achieve because of dissimilar physical and mechanical properties. In this study, a direct brazing process was successfully demonstrated to bond sapphire to sapphire and sapphire to Inconel 600 using BAg-8 + 1.5Ti filler metal. Silver-based brazing filler metal with active element of Ti was believed to promote wetting in brazing of ceramic surfaces. The results have shown that a reaction layer is present between the sapphire and the brazed layer. There is also a variation in the phase formation between the sapphire/sapphire and the sapphire/Inconel 600 joints because of the influence of elements from the Inconel 600.